Theory of sketches for database mappings. (2015) - Majkić, Zoran; Prasad, Bhanu
This paper presents two basic operations, separation and data federation, for database schemas that are used in database mapping systems and explains why functorial semantics for database mappings need a new base category instead of usual Set category. A definition of graph G for a schema database mapping system and the definition of its sketch category Sch(G) are presented. Based on this framework, functorial semantics for database mapping systems with the new base category DB are also presented.